Kolaborasi Lintas Sektor dalam Penanggulangan Gelandangan dan Pengemis di Perkotaan - Muhammad Hikmal; Ihyani Malik; Nur Wahid (Department of Public Administration, Muhammadiyah University of Makassar, 2024)
Increased numbers of beggars and homeless people can lead to a decline in the quality of life in urban areas, as well as increased social tensions and inequality. This situation can also lead to social stigmatisation of this vulnerable group, which then worsens their condition and complicates efforts to reintegrate into society. The purpose of this research is to analyse the role of the Pinrang Regency government in handling vagrants and beggars. The type of research used is a qualitative approach with a qualitative description research type. The results showed that the Social Service and Satpol PP collaborated in handling vagrants and beggars in Pinrang Regency. However, the findings are that the cooperation has not been effective. The results of the research conducted revealed that the role of the Social Service in handling vagrants and beggars in Pinrang Regency still has not reached the expected level of effectiveness. Although planning has been carried out by Satpol PP and the Social Service of Pinrang Regency, the results obtained do not meet expectations.